STUDI PENENTUAN LOKASI BUOY TSUNAMI DI SAMUDERA INDIA SELATAN JAWA-BALI - Dwi Haryanto; Adam Budi Nugroho; Muhamad Irfan; Yudo Haryadi (Laboratory for Marine Survey Technology, 2021)
[Study for Determination of Tsunami Buoy Location in Indian Ocean of Southern Java-Bali]. Indonesia is located on the border of three tectonic plates that slide over each other, the Indo-Australian Plate, the Pacific Plate, and the Eurasian Plate. This relative movement between tectonic plates can cause tectonic earthquakes in the sea. Tectonic earthquakes at sea are one of the main causes of tsunamis in Indonesia. Ina-Buoy is a tsunami warning technology system that includes sensors installed on the seabed (ocean bottom unit (OBU)) and these sensors send signals to a surface buoy station that floats on the sea surface using a mooring system. The installation of a tsunami buoy must be in the right location and consider several parameters, namely: depth parameter, seabed gradient, and seabed material type. A study for determination of tsunami buoy locations in Southern Java-Bali based on a three-parameter assessment has resulted in three appropriate locations for tsunami buoy installation. The first locations is in southern Malang at coordinates 112°31'34”E, 9°11'41”S which has a depth of 2042m, seabed gradient of 2° or 2.5%, and the type of seabed material is greenish ash clay with thickness of about 20 cm. The second locations is in southern Sunda Strait at coordinates 104°00'22”E, 6°30'19”S which has a depth of 2038m , seabed gradient of 0.31° or 0.5%, and the type of seabed material is greenish ash claym with thickness of about 25 cm. While the third location is in Southern Bali at coordinates 115°12'37.52E, 9°44'22.38S which has a depth of 4282.5m, seabed gradient 0.31° or 0.5%, and the type of seabed material is the form of ash clay with Brownish with thickness of about 30 cm. Keywords: Tsunami buoy, sea water depth, gradient, and type of seabed material